2012
DOI: 10.1037/a0026711
|View full text |Cite
|
Sign up to set email alerts
|

Perceived utility of emotion: The structure and construct validity of the Perceived Affect Utility Scale in a cross-ethnic sample.

Abstract: This study introduces a new measure of the perceived utility of emotion, which is the degree to which emotions are perceived to be useful in achieving goals. In this study, we administered this new measure, the Perceived Affect Utility Scale (PAUSe), to a sample of 142 European American and 156 East Asian American college students. Confirmatory factor analyses provided support for a new, culturally informed parsing of emotion and for perceived utility of emotion to be distinguishable from ideal affect, a relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 29 publications
4
33
0
Order By: Relevance
“…In the current research we differentiated emotions on the bases of the following two dimensions: (a) positive versus negative valence; and (b) self-centered versus other-centered (Chow & Berenbaum, 2012). Our decision to parse emotions based on positive versus negative valence is based on a wealth of emotion research demonstrating the stability and robustness of this dimension (e.g., Feldman Barrett & Russell, 1999;Russell, 1991;wierzbicka, 1992).…”
Section: Interpersonal Conceptualizations Of Emotionmentioning
confidence: 97%
See 4 more Smart Citations
“…In the current research we differentiated emotions on the bases of the following two dimensions: (a) positive versus negative valence; and (b) self-centered versus other-centered (Chow & Berenbaum, 2012). Our decision to parse emotions based on positive versus negative valence is based on a wealth of emotion research demonstrating the stability and robustness of this dimension (e.g., Feldman Barrett & Russell, 1999;Russell, 1991;wierzbicka, 1992).…”
Section: Interpersonal Conceptualizations Of Emotionmentioning
confidence: 97%
“…Although perceptions of emotional utility, like virtually all emotion variables, can be context-specific (e.g., Tamir et al, 2007), research has also found that they are linked to stable factors, such as personality traits (e.g., Chow & Berenbaum, 2012;Tamir, 2005Tamir, , 2009Tamir & Ford, 2012). For example, individuals high in certain personality traits (e.g., neuroticism) will choose to increase their level of specific emotional states (e.g., worry) because doing so provides utilitarian benefits (e.g., being aware of threat; Tamir, 2005).…”
Section: Utilitarian Considerations In Emotionmentioning
confidence: 99%
See 3 more Smart Citations